Nutritional Indexes as Predictors of Survival and Their Genomic Implications in Gastric Cancer Patients. (14th September 2021) - Sánchez, Yesennia; Vaca-Paniagua, Felipe; Herrera, Luis; Oñate, Luis; Herrera-Goepfert, Roberto; Navarro-Martínez, Guiselle; Cerrato, Dennis; Díaz-Velázquez, Clara; Quezada, Ericka Marel; García-Cuellar, Claudia; Prada, Diddier
Abstract: Gastric cancer is an aggressive malignancy with poor prognosis. Although obesity is a risk factor, an association between overweight and better survival has been reported. We explored the genomic implications of such association. Data from 940 patients were analyzed using Cox regression models and ROC curves to assess body mass index (BMI) and prognostic nutritional index (PNI) as predictors of survival. The exome sequencing of a random subset was analyzed to determine copy number variation (CNV) and single nucleotide variation (SNV), using Kruskal-Wallis and chi-square tests to evaluate their clinical implications. Overall survival was lower in patients with BMI ≤ 24.9 and PNI ≤ 29 ( p < 0.001). BMI and survival were directly correlated (HR: 0.972, 95% CI: 0.953, 0.992; p -value < 0.007). A higher PNI correlated with improved survival (HR: 0.586, 95% CI: 0.429, 0.801; p -value <0.001). We found a PNI cutoff point of 41.00 for overall survival. Genomic analysis showed an association between lower BMI, less CNV events ( p -value = 0.040) and loss of tumor suppressor genes ( p -value = 0.021). BMI and PNI are independent factors for overall survival in gastric cancer, probably linked to variations in genomic intratumoral alterations.